What aspects of group work influence learner experience at Cranfield University? - Chivers, Judith (Cranfield University, 2017)
Employers consider the ability to work in groups essential and higher education has adopted group working in programmes to meet this necessity. However, current reporting fails to identify which aspects are positively or negatively associated with students’ experiences. Therefore the phenomena of interest in this study are the use of group working in taught Masters level programmes as preparation for learners’ subsequent professional work and those aspects of group work which influence their experience. An exploratory qualitative study was undertaken using semi-structured, one to one interviews as the primary source of data. Interviews were undertaken with students, module leaders and programme directors from four modules on four different programmes from Cranfield University. The findings showed how the principle of providing students with realistic experiences of their disciplines in a working environment governed decisions on task and selection. Learners reported varying prior experience of group work, difficulties in understanding how to work in groups and a perception of little support from their instructors. Training on effective group working was inadequate. Descriptions of unequal contribution were widespread, though this was not recounted as being related to the international nature of the groups. Learners overall had a positive experience and found activities supported their technical learning and familiarity with industry’s working methods. The research indicated direct contact with clients was of greater benefit and was a stimulus for students. The assumptions regarding students’ previous experiences and learning about group processes, linked to the lack of training they received, resulted in poor experiences in this respect. Training was presented as the area most requiring improvement. Enhancements would offer opportunities to support engagement by students in addressing conflict, interpersonal relations and perceived failure to contribute. Similarly, training instructors on facilitation would lead to better resolution of unacceptable group working practices.
Keywords: Student experience; Learner experience; Group work; Teamwork